Using Technology With Future Teachers Of Primary School Mathematics: A Glimpse Into An American Experience - Abramovich, Sergei (Computer Tools in Education, 2021)
The paper describes the author’s experience in using technology within mathematics content and methods (undergraduate and graduate) courses for prospective teachers of primary grades (age 5–10). The main pedagogical idea behind the courses is to change pre-teachers’ perception of mathematics as a subject matter most people predictably dislike. It is suggested that technology can assist instructors in making mathematics an enjoyable subject matter without sacrificing content. The paper provides examples of using Excel, Wolfram Alpha, dynamic geometry software, computer graphing program, and theOnline Encyclopedia of Integer Sequences. In conclusion, solicited comments by teacher candidates about their experience of learning computer assisted mathematics are shared.
Keywords: mathematics, teacher education, primary grades, Excel, Wolfram Alpha, Ge- ometer’s Sketchpad, the Graphing Calculator, OEIS®.